Nasal Polyposis: An Experience in Mid and Far Western Region of Nepal - Sharma, A; Saxena, RK; Verma, L R (Journal of Nepalgunj Medical College, 2018)
Background: Nasal polyposis is an unpleasant disease in the developing countries which severely interferes with quality of life but still there is a lack of data on nasal polyposis in Mid and Far Western Region of Nepal. Aim of study: The aim of this hospital based study was to find out the distribution, patterns, presentations and management of nasal polyposis in Mid and Far Western Region of Nepal with a view to improve our understanding of its clinical and epidemiological characteristics. Methods: This prospective descriptive study was conducted from January 2015 to June 2016 in 80 patients diagnosed clinically as nasal polyposis, in the department of otorhinoloryngology, Nepalgunj Medical College Teaching Hospital, Kohalpur. Results: The most common age group affected in the study was comparatively younger ranging from 10-20 yrs. Ethmoidal Polyp were more frequent than antrochoanal polyp (56.25% vs 43.75%). Antrochoanal polyp were more common among the younger age groups 10-20 yrs (30%) where as the ethmoidal polyp were more common among higher age group. All antrochonal polyps (100%) were unilateral while majority of the ethmoidal polyps (89%) were bilateral. The main presenting clinical features were nasal obstruction (100%), nasal discharge (93.75%), sneezing (72.5%) and headache (40%). Conclusion: Nasal polyposis is common in Mid and Far western region of Nepal. Ethmoidal polyps are more common than antrochoanal polyps and are usually bilateral. Antrochoanal polyps are unilateral and mostly present in 10-20 yrs age group patients. Patients usually present late when the polyps are large. NGMC, Vol. 14 No. 2 December 2016, Page: 15-17